Implementation of Digital Marketing Through Instagram In Improving Marketing Communication of Al-Fath Muslim Lifestyle: A Case Study of Al-Fath Muslim Lifestyle - Chikal Prioputra (Penerbit Jurnal Indonesia, 2026)
This study examines the implementation of digital marketing through Instagram as a marketing communication strategy for Al-Fath Muslim Lifestyle, a retail fashion brand under Margaria Group in Yogyakarta. Using a qualitative descriptive approach, data were collected through in-depth interviews, observations, and documentation to understand how Instagram supports communication processes, customer engagement, and brand visibility. The analysis is guided by Luttrell’s (2015) Circular Model of Social Media (Share, Optimize, Manage, Engage). Findings indicate that Al-Fath effectively utilizes Instagram features—such as Instafeed, Instastory, reposts, and Instagram Ads—to enhance brand awareness, increase audience reach, and strengthen customer relationships. Optimization through bio links, consistent posting timelines, and content curation further improve visibility and engagement. However, engagement through interactive formats such as quizzes and community-based content remains limited. The study concludes that Instagram serves as an essential tool for modern marketing communication and recommends improving interactive strategies to deepen consumer involvement.